Fitonematoda pada Tanaman Jambu Biji - Kurniawati, Fitrianingrum; Kumala, Ayang Ratna (Jurnal Fitopatologi Indonesia, 2021)
Phytonematodes on Guava PlantSymptoms of disease by phytonematodes were found in guava plantations in Cibening Village, Pamijahan District, Bogor Regency, West Java. Diseased plants show symptoms, including stunted plants, yellowing leaves, root necrotic and root knots. Nematode extraction was carried out from 100 mL of soil and 5 g of guava root samples. Identification was carried out morphologically by observing the key characters of each genus of phytonematodes found. Counting the number of nematodes was carried out for each genus. Six genera of phytonematodes were identified, namely Criconemoides, Helicotylenchus, Hoplolaimus, Meloidogyne, Rotylenchulus, and Xiphinema with numbers ranging from 8 to 2300 individuals. This paper is the first report of parasitic nematodes on guava in West Java Province.